Xiaoyao San ameliorates maternal inflammation-induced neurobehavioral deficits by modulating the microbiota-gut-brain axis in offspring - Lin, Chunqiao; Zhu, Jiushuang; Zhang, Lu; Shi, Lijie; Zhong, Zhuoting; Xia, Xiuwen; Ding, Weijun; Yang, Youjun (Frontiers in Pharmacology, 2025)
BackgroundXiaoYao San (XYS), a classical Traditional Chinese Medicine (TCM), has demonstrated efficacy in alleviating stress-related neuropsychiatric disorders. However, its therapeutic potential against maternal immune activation (MIA)-induced neurobehavioral impairments remains unexplored. This study aims to investigate the neuroprotective effects of XYS on MIA-related behavioral dysfunctions and elucidate its underlying mechanisms.ResultsUsing a poly (I:C)-induced MIA mouse model, we demonstrated that XYS effectively ameliorates autism spectrum disorder (ASD) related behavioral phenotypes. Mechanistic investigations revealed that XYS exerts its therapeutic effects through: (1) Attenuation of core behavioral deficits including enhanced social interaction and reduced repetitive behaviors; (2) Downregulation of intestinal amino acid transporters; (3) Restoration of cerebral glutamate-GABA balance via modulation of glutamine pathway; (4) Structural remodeling of gut microbiota with specific enrichment of Bacteroides spp. Notably, B. uniformis was identified as a key microbial mediator capable of recapitulating XYS-mediated neurophysiological improvements through metabolic regulation.ConclusionThis study elucidates XYS as a multi-target therapeutic agent that coordinately modulates gut microbial ecosystems, amino acid homeostasis, and neurotransmitter homeostasis. The findings provide novel insights into the gut-brain axis mechanisms of TCM formulations, offering a scientific foundation for developing microbiota-based intervention strategies for neurodevelopmental disorders.